1998
DOI: 10.1086/231295
|View full text |Cite
|
Sign up to set email alerts
|

The Long‐Term Effects of Foreign Investment Dependence on Economic Growth, 1940–1990

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org..

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
100
2
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(112 citation statements)
references
References 13 publications
4
100
2
3
Order By: Relevance
“…2 Firebaugh (1992) critiques these early world systems and dependency studies for faulty interpretations. Recently, several studies that take into account Firebaugh's critique still find negative effects of longterm FDI on economic growth and income inequality (Alderson and Nielsen 1999;Dixon and Boswell 1996;Kentor 1998), while De Soysa and O'Neal (1999) largely replicate Firebaugh's findings. In addition, some studies conclude that FDI has no effect on economic growth (Dutt 1997;Hein 1992).…”
Section: Global Economy As Instituted Process--129mentioning
confidence: 99%
“…2 Firebaugh (1992) critiques these early world systems and dependency studies for faulty interpretations. Recently, several studies that take into account Firebaugh's critique still find negative effects of longterm FDI on economic growth and income inequality (Alderson and Nielsen 1999;Dixon and Boswell 1996;Kentor 1998), while De Soysa and O'Neal (1999) largely replicate Firebaugh's findings. In addition, some studies conclude that FDI has no effect on economic growth (Dutt 1997;Hein 1992).…”
Section: Global Economy As Instituted Process--129mentioning
confidence: 99%
“…This intervention was followed by a lively round of rebuttal-and-response without a clear victor (Dixon and Boswell 1996a;c.f. de Soysa and Oneal 1999;Kentor 1998). Others claimed that even though the deleterious link between FDI and development hinged critically on long-term processes of "disarticulation" in host economies, analysts misspecified their models by regressing economic growth on long-term lags of FDI without considering contemporaneous variation on FDI (de Soysa and Oneal 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Throughout history various approaches have been found to stimulate growth, from mercantilist protectionism of the sixteenth to eighteenth centuries, to command economy of socialism, to embedded autonomy that drove the growth of the Asian Tigers, among others (Bandelj & Sowers 2010). Moreover, much research in the sociology of development, adopting world-systems and dependency theoretical lenses points to negative consequences of foreign investment (Dixon & Boswell 1996;Kentor 1998Kentor , 2001de Soysa & Oneal 1999;Alderson & Nielsen 2002;Beer & Boswell 2002;Alderson 2004;Mahutga & Bandelj 2008). Further, recent studies on the link between FDI and growth have actually found a negative relationship (Herzer 2012;Curwin & Mahutga 2014).…”
Section: The Interplay Of Neoliberal Globalisation and Postsocialist mentioning
confidence: 99%